Economic Development and Environmental Protection Based on the Use of Natural Tourist Attractions and Supply Chain Management in Kosovo - Bedri Millaku; Adem Dreshaj; Afrim Selimaj (International Journal of Supply Chain Management, 2018)
Each country has some potential tourist attraction. Although, Kosovo is the small country, it possesses multiple tourist values ​​, which can be used as tourist potential. The use of natural potential values ​​for tourism is important component for economic development and environmental protection of each country. In most countries, these values use more than possible. In fact, increasing environmental preservation will create favorable economic development in the context of social welfare for the population and young labors. The use of natural potentials in order to coordinate tourism is the good way for environmental protection and economic development. However, the economic development will establish the gross products for country. In this paper, we will study how to set up the tourist offer and list the rightful places for economic development based on supply chain management. Key words: Natural tourist attractions, economic development, environmental protection, Kosovo, supply chain management.